Might Oral Human Papillomavirus (HPV) Infection in Healthy Individuals Explain Differences in HPV-Attributable Fractions in Oropharyngeal Cancer? A Systematic Review and Meta-analysis. (22nd December 2018) - Mena, Marisa; Taberna, Miren; Monfil, Laura; Arbyn, Marc; de Sanjosé, Silvia; Bosch, Francesc Xavier; Alemany, Laia; Bruni, Laia
Abstract : New key estimates of oral human papillomavirus (HPV) infection and insights on the relationship between oral infection and HPV-associated oropharyngeal cancer are presented. Observed differences in HPV-attributable fractions in oropharyngeal cancer cannot be explained by difference in the prevalence of oral HPV infection across healthy populations. Abstract: Background: Differences in oral human papillomavirus (HPV) prevalence and contrasts in HPV-attributable fractions (AFs) in oropharyngeal cancer (OPC) have not been evaluated in depth. Methods: A systematic review was performed to identify studies in which at least 50 healthy individuals were tested for oral HPV infection. Information on sex, age, tobacco/alcohol consumption, sex practices, specimen collection, HPV detection, and population type was extracted. Prevalences were pooled using random-effects models for meta-analyses of binomial data. Correlations were assessed by the Spearman test. Results: Forty-eight reports comprising 28 544 individuals fulfilled inclusion criteria. Global oral HPV prevalence was 4.9%. Estimates were highest in Europe, although regional differences were not statistically significant. HPV16 prevalence was 1.0% globally, and regional differences became statistically significant. A lifetime history of >6 sex partners showed a higher risk of oral HPV infection. The age-specific HPV distribution revealed a prevalence of ≥5% over 40 years of age and a lower prevalence at younger ages. There was no association between oral HPV prevalence and HPV-AFs or age-standardized rates (ASRs) of OPC, genital HPV in healthy women, or tobacco use. Conclusions: Differences in HPV-AFs or ASRs of OPC cannot be explained by differences in the prevalence of oral HPV infection across healthy populations. Consistent research on determinants of oral HPV prevalence, acquisition, clearance, and persistence is warranted.